Association of Human Whole Blood NAD+ Contents With Aging - Yang, Fan; Deng, Xuan; Yu, Ye; Luo, Lei; Chen, Xianda; Zheng, Jinping; Qiu, Yugang; Xiao, Feng; Xie, Xiaomei; Zhao, Yuzheng; Guo, Jun; Hu, Feifei; et al. (Frontiers in Endocrinology, 2022)
Background: NAD+, nicotinamide adenine dinucleotide, is mostly described to associate with aging process. We aimed to investigate the association between human whole blood NAD+ contents and aging in a relative large-scale community-based population and further to address the gender impact on this association. Methods: We recruited 1518 participants aged over 18 years old and free of cardiovascular and any type of cancer from Jidong community from 2019 to 2020. Whole blood NAD+ level was measured by cycling assay and LC- mass spectroscopy assay. The chronological age and clinical data were collected using standard questionnaires. The participants were divided into five groups according to their chronological age. General liner regression model was performed to analyze the association between NAD+ contents and aging. In addition, we also conducted subgroup analysis by gender. Results: The mean age of included 1518 participants was 43.0 years, and 52.6% of them were males. The average levels of whole blood NAD+ of total participants was 33.0±5.5 μmol/L. The whole blood NAD+ contents in males were significantly higher than that in females (34.5 vs. 31.3 μmol/L). There was significant difference in the meat diet among NAD+ quartile groups (p=0.01). We observed a decline trend of NAD+ contents with aging before 50 years in total participants with significant level in 40-49 years old group (β coefficients with 95% confidence interval (95% CI): -1.12 (-2.18, -0.06)), while this trend disappeared after the 50 years. In addition, this association was significantly altered by gender (p for interaction=0.003). In males, as compared with ≤29 years group, adjusted β coefficient decreased with aging but was only significant in the ≥60 year group (β , -2.16; 95% CI, -4.16 to -0.15). In females, the level of whole blood NAD+ did not significantly differ among five age groups and without the trend as males. Conclusions: Association of whole blood NAD+ contents with aging significantly differed in males and females. The loss of blood NAD+ with aging only was observed in males, especially in the male middle-aged population. It is crucial to consider the gender difference in further NAD+ related studies in the future.